EFFECTS OF A SIX-WEEK STRENGTH TRAINING AND UPPER BODY PLYOMETRICS IN MALE COLLEGE BASKETBALL PHYSICAL EDUCATION STUDENTS - Jennifer G. Inovero; Jeffrey C. Pagaduan (Sport Scientific And Practical Aspects, 2025)
This study investigated the effects of a six-week resistance training with upper body plyometrics in the performance of male college students in a basketball physical education (PE) class. Sixteen males in a novice class in a college basketball PE were randomly assigned into two groups. The experimental group (EXP; age: 17.4 ± 0.74 years; height: 1.66 ± .04 m; weight: 61.3 ± 7.6 kg) performed a combined strength and plyometric training twice a week for six weeks. Also, EXP underwent a once a week basketball training (2 hours) separated from strength with plyometric sessions. The control group (CON; age: 17.8 ± 1.28 years; height: 1.65 ± .03 m; weight: 60.6 ±8.2 kg) only participated in two hours a week of basketball skills training. Pre-test and post-test upper body strength, grip strength, vertical jump, and American Alliance for Health, Physical Education, Recreation and Dance (AAHPERD) battery of tests for basketball were gathered. Results showed a significant main interaction of intervention and test time on passing skill at F(1, 7) = 0.50, p < 0.05, partial η2 = 0.07. In conclusion, a six-week strength and upper body plyometrics posted a significantly lower passing score than the control.